A novel algorithm of the perfectly matched layer based on the Runge–Kutta method of order 2 accuracy - Li, Kun‐Lai; Zhang, Yongliang; Li, Jianxiong (Microwave and optical technology letters, 2023)
The perfectly matched layer (PML) has the ability to terminate the finite‐difference time‐domain (FDTD) lattice successfully. It is crucial to investigate the interaction between electromagnetic waves and the PML. Utilizing the Runge–Kutta method of order 2 accuracy, we derive a novel and efficient complex frequency‐shifted (CFS) PML implementation algorithm, which is named the RK‐PML. To validate the RK‐PML, we provide two numerical examples, which include rectangular waveguide and plasma cube truncated by the PML. By analyzing the time‐domain relative reflection errors, the frequency‐domain reflection coefficients, the computational time, and the memory footprint, the proposed RK‐PML outperforms slightly the convolutional PML (CPML).